PERFORMANCE ANALYSIS OF MONEY MARKET MUTUAL FUNDS, FIXED INCOME MUTUAL FUNDS, MIXED MUTUAL FUNDS, AND STOCK MUTUAL FUNDS IN INDONESIA DURING THE 2015-2020 PERIOD - Jessica Claudia Mawikere (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2022)
Mutual funds as one of the investment instruments in Indonesia continue to grow and try to provide product choices with the maximum possible return. Investors need good mutual fund knowledge in order to be able to take the right steps according to the type of each investor in investing. This research aims to analyze the performance of money market mutual funds, fixed income mutual funds, mixed mutual funds, and stock mutual funds in Indonesia in the period 2015-2020. This performance measurement is done using Sharpe's Measure, Treynor's Measure, Jensen's Measure, and Appraisal Ratio. The results showed that it is not easy to maintain the best fixed mutual fund performance. While the worst performance for each year has similarities in certain mutual fund products. Keywords: Performance, Money Market Mutual Funds, Fixed Income Mutual Funds, Mixed Mutual Funds, Stock Mutual Funds, Sharpe, Treynor, Jensen, Appraisal Ratio.